Penjadwalan Produksi pada Mesin Paralel dalam Proses Pembuatan Produk Botol Kemasan - Ciptomulyono, Udisubakti (Jurnal Teknik Industri, 2008)
PT Abadi Adimulia is a company that work in plastic container production. The job arrival is static and the difference of processing time between the main process and the other process is very long. Until now the company use the First Come First Serve (FCFS) method to schedule their production activities, but with this method often the company finish their job over the due. The objective of this research was to obtain the production scheduling that give the minimum value in maximum lateness, makespan, number of late job, and the average tardiness on the blow mouldings machine. The production scheduling method that used in this research were Longest Processing Time method (LPT), Shortest Processing Time method (SPT), and Earliest Due Date method (EDD). The result from the scheduling using the three method indicate that LPT method is the best method to apply in this case which reduce the maximum lateness for 112.27 hours, makespan for 101.93 hours, number of late job for two jobs, and the average tardiness for 4.67 hours/job on June, maximum lateness for 60.07 hours, makespan for 123.19 hours, number of late job for one jobs, and the average tardiness for 2.5 hours/job on June, and maximum lateness for 53.42 hours, makespan for 38.1 hours, number of late job for one jobs, and the average tardiness for 2.05 hours/job on June.